Análise de livro didático dos anos iniciais do Ensino Fundamental: conteúdos de Estatística descritiva e o Sistema de Avaliação do Rendimento Escolar do Estado de São Paulo (SARESP) - Golfeti, Silvia Marques (2017)
The present research reports a bibliographic study involving textbooks and large scale evaluation, System of Evaluation of School Income of the State of São Paulo (SARESP). The objective was to investigate the mathematical praxeologies contained in textbook activities, in order to verify if they have the potential the prepare the student to develop statistical knowledge requested in the SARESP. The research involved the textbooks adopted in public school network of the São Paulo State, from the National Program of Didactic Book of the federal government for the initial grades of elementary school. The methodological procedures adopted were the exploration of the chosen documents, the analysis process being based on the Anthropological Theory of Didactics (ATD) and based on the levels of table comprehension, according to Wainer and graphs, according to Curcio. The main result obtained with the research was the verification that the textbooks prepare the subjects, submitted to the practice of these manuals for the levels of comprehension of graphs and tables, with superiority of those required in the SARESP, And the levels of understanding identified in the praxeologies of the activities of this evaluation are expressed below what is prescribed in the national curricular references